Metode Multisensori Sebagai Penanganan Kesulitan Membaca Siswa Retardasi Mental - Evie Syalviana (LPPM IAIN Parepare, 2019)
the purpose of this study to see is the multisensory method effective to improve reading ability for mental retardation students who have reading difficulties. Subjects ini this study were elementary school students who were diagnosed with special mental retardation dan had reading diffculties in the early classes, namely grades 1 dan 2 of elementary school. The research design used the classical experimental design. The classical experimental design consisted of randomized, control group, the experimental group, pretest and posttest. The technique of collection data uses a reading test at the pretest and postest. The results of this study was the multisensosy methodeffective to improve reading ability for mental retardation students who have reading difficulties.